2010
DOI: 10.1186/1471-2334-10-330
|View full text |Cite
|
Sign up to set email alerts
|

Travel and migration associated infectious diseases morbidity in Europe, 2008

Abstract: BackgroundEuropeans represent the majority of international travellers and clinicians encountering returned patients have an essential role in recognizing, and communicating travel-associated public health risks.MethodsTo investigate the morbidity of travel associated infectious diseases in European travellers, we analysed diagnoses with demographic, clinical and travel-related predictors of disease, in 6957 ill returned travellers who presented in 2008 to EuroTravNet centres with a presumed travel associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
10

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 28 publications
6
64
1
10
Order By: Relevance
“…Even though the proportionate morbidity data presented in this and previous [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] studies are very informative, the incidence figures are of special value, as they describe more accurately the risks for travellers and, as illustrated in Figure 3, allow comparisons between various regions. Our study sample represents the most severe cases, yet the actual incidence of health problems among travellers needing medical care abroad may in reality be sixfold higher than that presented here (Figure 1).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the proportionate morbidity data presented in this and previous [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] studies are very informative, the incidence figures are of special value, as they describe more accurately the risks for travellers and, as illustrated in Figure 3, allow comparisons between various regions. Our study sample represents the most severe cases, yet the actual incidence of health problems among travellers needing medical care abroad may in reality be sixfold higher than that presented here (Figure 1).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Assessment of travellers' health problems has largely been based on calculations of proportionate morbidity of returning travellers as reported by specialised centres for travel and tropical medicine [3][4][5][6]. Data on illness or injury while abroad have been collected chiefly after travel from questionnaires, telephone surveys [2,[7][8][9][10][11][12][13][14] and insurance claims [15,16], data recorded during actual travel are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…10 Surveillance data indicate that dengue is now the most common cause for fever in travellers returning from all geographical regions except sub-Saharan Africa and Central America, where malaria remains the most common cause. 11,12 Travellers returning to Europe usually acquire dengue from South-East Asia, particularly Thailand, 13 while in the USA the highest rates followed travel to Dominican Republic and Mexico. 14 Autochthonous spread has been reported from the south of France and Croatia, and in 2012 the fi rst European dengue outbreak since the 1920's occurred in Madeira, resulting in over 2,000 cases and 120 hospitalisations.…”
Section: Dengue In Non-endemic Areasmentioning
confidence: 99%
“…9,10 Several studies have shown that the most prevalent symptoms among travelers and immigrants were diarrhea, fever, and skin disorders. 6,11,[18][19][20] In some studies that compared travelers with immigrants whose purpose of travel was VFR, the risk of acute diarrhea was higher among travelers, whereas the risk for malaria and viral hepatitis was higher among VFRs. 21 The findings mentioned above were considered when patients consulted the Department of Infectious Diseases and Tropical Medicine (DITM) of the University of Munich, Germany.…”
Section: Introductionmentioning
confidence: 99%